2015
DOI: 10.1039/c5dt02709h
|View full text |Cite
|
Sign up to set email alerts
|

Halocuprate(i) zigzag chain structures with N-methylated DABCO cations – bright metal-centered luminescence and thermally activated color shifts

Abstract: Two compounds 1,4-dimethyl-1,4-diazoniabicyclo[2.2.2]octane catena-tetra-μ-halo-dicuprate(I) with DABCOMe2 Cu2X4 (1: X = Br, 2: X = I) were synthesized by hydrothermal reaction of copper(I) halides with the corresponding 1,4-diazoniabicyclo[2.2.2]octane (DABCO) dihydrohalides in an acetonitrile/methanol mixture. Both compounds crystallize monoclinically, 1 with a = 9.169(4) Å, b = 10.916(6) Å, c = 15.349(6) Å, β = 93.93(2)°, V = 1533(1) Å(3), Z = 4, space group P2(1)/n (no. 14) and 2 with a = 15.826(9) Å, b = … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Among the various alternatives, low-dimensional cuprous-based metal halides have attracted much attention owing to their high PLQY, earth abundance, and low cost, and low toxicity. For example, Jun et al reported a kind of zero-dimensional (0D) Cs 3 Cu 2 I 5 single crystals (SCs) with coexisting tetrahedral and trigonal Cu + sites and a highly efficient blue emission (PLQY ∼ 90%) . Li et al successfully prepared high-quality CsCu 2 I 3 SCs by an antisolvent vapor-assisted method and developed a high-speed UV-to-vis photodetector .…”
Section: Introductionmentioning
confidence: 99%
“…Among the various alternatives, low-dimensional cuprous-based metal halides have attracted much attention owing to their high PLQY, earth abundance, and low cost, and low toxicity. For example, Jun et al reported a kind of zero-dimensional (0D) Cs 3 Cu 2 I 5 single crystals (SCs) with coexisting tetrahedral and trigonal Cu + sites and a highly efficient blue emission (PLQY ∼ 90%) . Li et al successfully prepared high-quality CsCu 2 I 3 SCs by an antisolvent vapor-assisted method and developed a high-speed UV-to-vis photodetector .…”
Section: Introductionmentioning
confidence: 99%
“…Coordination polymers (CPs) are a large group of compounds which depending on the selected building blocks (metal ions and organic ligands) have a great structural variety and an immense diversity of physical and chemical properties. Thanks to their infinite structure and function tailorability that originates from the abundant building blocks, these materials can present, among other properties, interesting electrical conductivity. For instance, the paradigmatic case of MMX chains with platinum, iodine, and dithiocarboxylato ligands is particularly outstanding due to its high electrical conductivity even at room temperature, as well as the metallic to semiconducting phase transitions showed by them with the temperature. , Their intriguing features have also been analyzed at the nanoscale to demonstrate their potential as a source of novel molecular wires. , Indeed, several CPs show significant electrical conductivity. In this context, copper­(I) halides have been subjected to a number of studies, particularly for those with ligands with π* or σ* orbitals suitable for efficient d π metal orbitals overlapping. ,, As a result of their structural diversity, originating from the polymerization of copper–halogen-based subunits, double Cu–X chains are a subclass of CPs that can generate multifunctional materials showing combination of electrical conductivity and photoluminescence. ,, Moreover, the electrical conductivity found in some of the Cu–X double chains suggests their potential use as electronic materials . The features reported on copper­(I) double chains with iodide as bridging ligands are also noticeable, since they show interesting luminescent properties. ,,,, More recently, we have found that although this family of compounds shows rather similar structures the double Cu–I chain presents a high degree of structural flexibility, suggesting an elastic spring like behavior when these CPs are exposed to external physical and/or chemical stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…The emission lifetimes significantly increased with decreasing the temperature. This finding could be due to the relation of decreased non-radiative rate to the high spin-orbit coupling of Ag(I) ions and fast intersystem crossing 38 . This behavior is also observed in the emissive copper(I) and silver(I) complexes with the thermally activated delayed fluorescence 39,40 .
Figure 3Temperature-dependent emission spectra of single crystal 1 from 5 to 300 K. Inset: Images for single crystals under ambient light at room temperature (left), under 365 nm UV lamp irradiation at room temperature (middle) and in liquid nitrogen (77k) (right).
Figure 4Temperature-dependent emission spectra of 1 in ground powder state from 5 to 300 K. Inset: Images for powder sample under 365 nm UV lamp irradiation in liquid nitrogen (left) and at room temperature (right).
…”
Section: Resultsmentioning
confidence: 99%